ANALISIS REGULASI PINJOL PADA SENGKETA KONSUMEN YANG BERBASIS KEADILAN - Siagian, Asman; Rahmadany, Rahmadany; Istiawati, Sri (Universitas Harapan Medan, 2024)
This study analyzes online lending regulations (pinjol) in the context of justice-based consumer dispute resolution in Indonesia. The increasing number of consumer dispute cases in the financial technology (fintech) lending industry, especially online loans, shows a gap between existing regulations and their implementation in the field. Using a normative legal research method with a statutory and conceptual approach, this study aims to analyze the effectiveness of pinjol regulations in resolving consumer disputes and identify aspects that need to be strengthened to create a more equitable dispute resolution. Data were collected through literature studies and analysis of regulatory documentation related to pinjol and consumer protection. The results of the study indicate that existing pinjol regulations have not been fully able to provide optimal protection for consumers in resolving disputes. There are three main findings that are the main points that need to be highlighted: (1) there is still a lack of clarity regarding effective and efficient dispute resolution mechanisms, (2) weak supervision of unethical collection practices, and (3) lack of harmonization of regulations between relevant authorities in handling pinjol consumer disputes. This study recommends the need to strengthen regulations through: improving dispute resolution mechanisms, increasing supervision, and harmonization of regulations between relevant institutions. The theoretical implications of this study contribute to the development of a fintech regulatory concept that is more oriented towards consumer protection, while its practical implications provide input for policy makers in perfecting more equitable online loan regulations that favor the wider community.